STRUKTUR DAN PERILAKU INDUSTRI MASKAPAI PENERBANGAN DI INDONESIA TAHUN 2003-2007 - Baskoro Santorizki (Media Ekonomi, 2010)
The purpose of this study is to analyze market structure in Indonesia Airline Industry. Concentration ratio is used see the market structure and competition behavior. Seventeen (17) Airline Firm are used as sample for 2003-2007. We fad that airline industry in Indonesia face high oligopoly, competition so the best strategy of the firm in industry to win the competiton one price leadership, low cosh carrie, maintain the service and proposal.Keywords: Market stevence, Airline Industry, competitor behavior & strategy